2010
DOI: 10.1016/j.bone.2009.11.020
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of type I collagen morphologies in bone: Relation to estrogen depletion

Abstract: Bone is an amazing material evolved by nature to elegantly balance structural and metabolic needs in the body. Bone health is an integral part of overall health, but our lack of understanding of the ultrastructure of healthy bone precludes us from knowing how disease may impact nanoscale properties in this biological material. Here, we show that quantitative assessments of a distribution of Type I collagen fibril morphologies can be made using atomic force microscopy (AFM). We demonstrate that normal bone cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
120
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 69 publications
(127 citation statements)
references
References 22 publications
6
120
0
Order By: Relevance
“…6,7 Recent AFM studies indicated changes in the nanomorphology of the Type I collagen fibrils in ovariectomized (OVX) sheep [8][9][10] and rats. 11 In order to explore the effect of estrogen depletion and compare efficacy of CatKI and alendronate (ALN) drug treatments, the rabbit OVX model was developed by Merck Inc., as human CatKI's exhibit similar potency for the rabbit enzyme and the adult rabbit skeleton undergoes substantial cortical Haversian remodeling (unlike the rodent).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…6,7 Recent AFM studies indicated changes in the nanomorphology of the Type I collagen fibrils in ovariectomized (OVX) sheep [8][9][10] and rats. 11 In order to explore the effect of estrogen depletion and compare efficacy of CatKI and alendronate (ALN) drug treatments, the rabbit OVX model was developed by Merck Inc., as human CatKI's exhibit similar potency for the rabbit enzyme and the adult rabbit skeleton undergoes substantial cortical Haversian remodeling (unlike the rodent).…”
Section: Resultsmentioning
confidence: 99%
“…For the OVX treatment in Data Set II, an 18% decrease (P-value ¼ 0.0188) was observed in the proportion of fibril Figure S3). 8,9 Discussion OVX is a common model used to study the effects of estrogen depletion. 8,9,[15][16][17] Pennypacker et al 12 applied the OVX model to study osteopenia in rabbits using the samples described herein and demonstrated osteoclastic bone resorption resulting from estrogen depletion.…”
Section: Resultsmentioning
confidence: 99%
“…22,36 Each section was treated for 14 min with 0.5 M ethylenediaminetetraacetic acid at a pH of 8.0 followed by sonication for 5 min in water, and this cycle was repeated three times. Sections were imaged using a BioScope Catalyst AFM (Bruker, Santa Barbara, CA, USA) in peak force tapping mode.…”
Section: Atomic Force Microscopymentioning
confidence: 99%
“…At each location, 10-15 fibrils were analyzed in error images (B70 fibrils per bone) using two-dimensional fast Fourier transforms (2D FFTs) as described previously. [36][37][38][39] Briefly, 2D FFTs were performed on an area of interest over individual fibrils so that the first harmonic peak from the power spectrum represented the D-spacing for that fibril.…”
Section: Atomic Force Microscopymentioning
confidence: 99%
“…The presence of these distributions suggested to us that this metric may represent a means to observe changes that occur with disease in bone at the nanoscale. To date, we have shown that with ovariectomy-induced estrogen depletion in sheep [48] and Osteogenesis Imperfecta in mice [49], there are statistically significant shifts in the Dperiod distributions. Additional work is necessary to tie these changes in collagen morphology to alterations in mechanical function.…”
Section: Investigating Collagen In Bonementioning
confidence: 98%